University is Making Networks - Oleg A. Donskikh (Высшее образование в России, 2018)
This article is a review of a monograph “Innovation University: network perspective in partner associations” (Authors: Romm, M.V., Zayakina, R.A., Filatova, E.V., Luchikhina, L.F., Il’yin, S.E., published in Novosibirsk in 2018), which treats university activities in the context of the analysis of network unions. The monograph reveals the purposes, values, motives, and mechanisms of university network communication. The article shows the topicality of the authors’ approach to view university as an institute for socialization in conditions of instrumentalization and operationalization of education.